Cerebral oxygen saturation and cerebrovascular instability in newborn infants with congenital heart disease compared to healthy controls. - Nhu N Tran (Public Library of Science (PLoS), 2021)
Objective Infants with Congenital Heart Disease (CHD) are at risk for developmental delays, though the mechanisms of brain injury that impair development are unknown. Potential causes could include cerebral hypoxia and cerebrovascular instability. We hypothesized that we would detect significantly reduced cerebral oxygen saturation and greater cerebrovascular instability in CHD infants compared to the healthy controls. Methods We performed a secondary analysis on a sample of 43 term infants (28 CHD, 15 healthy controls) that assessed prospectively in temporal cross-section before or at 12 days of age. CHD infants were assessed prior to open-heart surgery. Cerebral oxygen saturation levels were estimated using Near-Infrared Spectroscopy, and cerebrovascular stability was assessed with the response of cerebral oxygen saturation after a postural change (supine to sitting). Results Cerebral oxygen saturation was 9 points lower in CHD than control infants in both postures (β = -9.3; 95%CI = -17.68, -1.00; p = 0.028), even after controlling for differences in peripheral oxygen saturation. Cerebrovascular stability was significantly impaired in CHD compared to healthy infants (β = -2.4; 95%CI = -4.12, -.61; p = 0.008), and in CHD infants with single ventricle compared with biventricular defects (β = -1.5; 95%CI = -2.95, -0.05; p = 0.04). Conclusion CHD infants had cerebral hypoxia and decreased cerebral oxygen saturation values following a postural change, suggesting cerebrovascular instability. Future longitudinal studies should assess the associations of cerebral hypoxia and cerebrovascular instability with long-term neurodevelopmental outcomes in CHD infants.